Ten-Year Experience With Stentless Aortic Valves: Full-Root Versus Subcoronary Implantation - Ennker, J.; Albert, A.; Rosendahl, U.; Ennker, I.; Dalladaku, F.; Florath, Ines (2008)
Background: We compared the midterm outcome after aortic valve replacement with the Freestyle stentless bioprosthesis for the full-root or subcoronary implantation technique, while adjusting for patient and disease characteristics by a propensity score. Methods: Between 1996 and 2005, 1,014 patients underwent aortic valve replacement with the stentless Medtronic Freestyle bioprosthesis, 168 using full-root technique. Based on a saturated propensity score, 148 matched pairs were created. Mean age of the 296 patients was 73 ± 3 years. Mean follow-up time was 32 ± 30 months (maximum, 116 months). Results: Operative mortality was 4.7% and 2.7% (p = 0.36) in the full-root and subcoronary groups, respectively. Freedom from reoperation, prosthetic valve endocarditis, major bleeding, and thromboembolism after 9 years was 98% ± 1% and 90% ± 7% (p = 0.38), 95% ± 3% and 92% ± 7% (p = 0.76), 72% ± 21% and 98% ± 2% (p = 0.12), and 75% ± 8% and 84% ± 7% (p = 0.28), for full-root and subcoronary groups, respectively. Survival rates after 9 years were 34% ± 24% and 33% ± 11% (p = 0.46), for the full-root and subcoronary groups, respectively. Patients in the full-root group received larger valve sizes (p = 0.03), and the mean transprosthetic gradients at discharge were significantly lower for each valve size. Nevertheless, during follow-up, peak gradients decreased to a greater extent in patients presenting high peak gradients (>36 mm Hg) at discharge. Conclusions: As risk-adjusted comparison of both implantation techniques did not reveal any differences regarding operative and midterm outcomes, full-root replacement can be liberally performed in patients with small aortic roots, annuloaortic ectasia, or requiring replacement of ascending aorta. © 2008 The Society of Thoracic Surgeons.